Mengenal Kehidupan Masyarakat Melalui Cerita Rakyat Toraja - Elisabet Mangera; Anastasia Baan; Berthin Simega; Resnita Dewi; Milka Milka; Rita Tanduk; Daud Rodi Palimbong; Monika Mangera (Institut Agama Islam Negeri Curup, 2024)
Folklore is a form of cultural heritage that is full of the life values, traditions and worldview of a society. This research aims to examine the life values ​​contained in Toraja folklore and how these values ​​reflect the social and cultural life of the Toraja people. The method used in this research is qualitative analysis with an ethnographic approach, where folk stories are collected and analyzed through in-depth interpretation. The research results show that Toraja folklore depicts the values ​​of togetherness, mutual cooperation, respect for ancestors, as well as respect and fear of customary law and cosmological rules. These values ​​not only function as a guide to life, but also strengthen Toraja cultural identity amidst ongoing social changes. These findings provide deeper insight into how folklore can be a medium for understanding social structures, moral values, and the Torajan people's perspective on life.